Handbook on sediment quality : a special publication (The Federation, 2002)
Annotation This first-of-its kind handbook is designed for environmental scientists and engineers dealing with water quality issues in water, wastewater or industrial treatment operations. Thoroughly addresses sorption processes, bioavailability, sediment collection and assessment techniques, toxicity testing, advantages and disadvantages of chemical sediment quality guidelines, and sediment quality modeling. This timely resource provides you with the knowledge and proposed solutions to identify assess and manage contaminated sediment. Both highly scientific and practically written, the Handbook on Sediment Quality provides detailed discussion of sediment geochemistry, toxicology, and water quality interactions.
Keywords: Sediments (Geology) -- Analysis.; elektronické knihy; electronic books